Odpowiedzialność biskupa diecezjalnego w procesie sądowym małżeńskim po ogłoszeniu motu proprio Mitis Iudex papieża Franciszka - Malecha, Paweł (Ius Matrimoniale, 2016)
In his motu proprio Apostolic Letter Mitis Iudex, Pope Francis underscores the role and responsibility of every Diocesan Bishop in the pastoral exercise of canonical justice and points out what must be done in the carrying out of the bishop’s own judicial power. The goal of this study is to bring together the teaching of the Pope and of the Church on the responsibility of the Diocesan Bishop in causes of marriage nullity. The question under study is not only presented in light of Mitis Iudex, but also takes into consideration other documents of the Holy See, especially those of the Apostolic Signatura, which sees to the correct administration of justice in the Church. For this reason the presentation of the topic is broader than its treatment in Mitis Iudex, and as a consequence it seeks a more comprehensive handling of the question at hand, naturally within the limits of such an article. In the first part of the study, questions of a doctrinal nature are dealt with, revealing, above all, that each Diocesan Bishop is the iudex natus of his own diocese. Therefore, he has not only the right, but also the duty – both of which have their origin in divine law – to judge coram Domino the cases of his faithful. In the next part, these rights and duties are presented, which then leads to an examination of the responsibility of the Diocesan Bishop in causes of marriage nullity. In the wake of the recent reforms – especially the elimination of the obligation to have a double conforming sentence and the introduction of the processus brevior – the responsibilities of the Diocesan Bishop are significantly amplified. In fact, in the pastoral exercise of his own judicial power, he must ensure that no laxism of any sort creeps in and that the truth is the foundation, mother, and law of justice in every aspect of the judicial process.